Diuresis and Arterial Pressure Modification in Anesthetized Wistar Rats, after Oral Administration of “Assa-Peixe” (Vernonia polyanthes Less.) Infusion (Revista Brasileira de Plantas Medicinais, 2000)
Vernonia polyanthes Less species, populary known as "assa-peixe" have been described as a medicinal plant. The balsamics, expectorantings and hemostactics properties of this plant are well known, making it an affective medicine to respiratory system diseases. The diurectic and hypotensive properties are little investigated, so the aim of this work is to study it. The infusion of this plant’s leaves was orally administered in anesthetized Wistar rats. The arterial pressure was evaluated by carotid artery canulation, conected to a manometer of mercury and the diuresis was registered by urinary bladder canulation. The rats of the control group received 1ml of physiological solution, while the animals of the expenmental group received 1ml of infusion of "assa- peixe", through an oral canula. The results showed a significant decrease in arterial pressure, as well a significant increase in urinary flux and sodium output. It is concluded that the "assa-peixe" infusion presents hipotensive and natridiurectic properties when administered to anesthetized Wistar rats.